Pinning for judges in harmonising Civil Law and Shariah: Challenges and prospects - Shuaib, Farid Sufian (2009)
Harmonisation of Civil and Shariah most of the time consider legislative process as the vehicle. Seldom do we consider achieving substantial harmonisation through judicial law making. Although judicial law making in itself may be problematic, this paper seeks to examine how judges could harmonise civil law and Shariah. This paper examines relevant judicial methods, training for legal professionals and appointment of judges. It is also the objective of this paper to look at challenges confronting such exercise and prospect in achieving harmonisation by judges.